Students’ underhand passing achievement in volleyball: roles of strength, coordination, and concentration - David Febrio; Alnedral Alnedral; Sepriadi Sepriadi; Yuni Astuti (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to examine the direct and indirect effects of arm muscle strength, hand–eye coordination, and concentration on underhand passing performance in junior volleyball athletes. A quantitative approach with path analysis was applied involving 30 male athletes from a school volleyball team using total sampling. Arm muscle strength was measured using the push-up test, hand–eye coordination using the wall toss test, concentration using the concentration grid test, and passing performance using a standardized underhand passing test. The results showed that arm muscle strength (β = 0.548), hand–eye coordination (β = 0.376), and concentration (β = 0.177) had significant direct effects on passing performance (p < 0.05). Indirect effects through concentration were also identified, although relatively small. The model explained 90.4% of the variance in passing performance. These findings indicate that underhand passing is influenced by physical, motor, and cognitive factors, highlighting the importance of integrated training approaches in volleyball development.